2019
DOI: 10.1103/physreve.100.022317
|View full text |Cite
|
Sign up to set email alerts
|

Explicit non-Markovian susceptible-infected-susceptible mean-field epidemic threshold for Weibull and Gamma infections but Poisson curings

Abstract: Although non-Markovian processes are considerably more complicated to analyze, real-world epidemics are likely non-Markovian, because the infection time is not always exponentially distributed. Here, we present analytic expressions of the epidemic threshold in a Weibull and a Gamma SIS epidemic on any network, where the infection time is Weibull, respectively, Gamma, but the recovery time is exponential. The theory is compared with precise simulations. The mean-field non-Markovian epidemic thresholds, both for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Similar cohort studies found heavier-tailed distributions based on power laws to be more compatible with the time intervals between successive interactions, citing the bursty nature of social dynamics as the determining factor [ 57 , 58 ], yet the corresponding data fit was often imperfect while extensive comparisons against exponentials were not performed. In the epidemiological setting, several authors have argued for a shift towards more realistic and flexible Gamma (more commonly Erlang [ 59 , 60 ]) or Weibull distributions [ 61 63 ] for the infection waiting times, emphasizing the non-Markovian behavior that epidemics occasionally exhibit. That being said, exponentials have been shown to provide a particularly good fit to epidemiological data when the mean generation time is correctly fixed [ 59 ] or the mean infection duration is smaller [ 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar cohort studies found heavier-tailed distributions based on power laws to be more compatible with the time intervals between successive interactions, citing the bursty nature of social dynamics as the determining factor [ 57 , 58 ], yet the corresponding data fit was often imperfect while extensive comparisons against exponentials were not performed. In the epidemiological setting, several authors have argued for a shift towards more realistic and flexible Gamma (more commonly Erlang [ 59 , 60 ]) or Weibull distributions [ 61 63 ] for the infection waiting times, emphasizing the non-Markovian behavior that epidemics occasionally exhibit. That being said, exponentials have been shown to provide a particularly good fit to epidemiological data when the mean generation time is correctly fixed [ 59 ] or the mean infection duration is smaller [ 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…and (1) = d 2 (z) dz 2 | z=1 = 1.97811 (see [28,Appendix]). Substituted in steady-state prevalence, (A7) gives us…”
Section: Estimate Of the Onset τ εmentioning
confidence: 99%
“…Using this theorem we calculate the generation time distribution for our model of infection propagation, and obtain a two parameter (effectively) distribution which can be used in epidemiological studies, as a logical replacement of hitherto used heuristic distributions, such as gamma, lognormal, Weibull, Gaussian etc. [26,27,31,32,41].…”
Section: The Distribution Of Generation Timementioning
confidence: 99%
“…The distribution of generation time or serial interval time for an infectious disease [24][25][26][27] is a very important quantity to understand the transmission potential, and to calculate the basic and effective reproduction number which is a key parameter to estimate the epi-demiological state of an infection in a population [28,29]. Until now, the distribution of generation time is estimated by fitting gamma, lognormal, Weibull, or Gaussian distributions to the transmission pairs data [26,[30][31][32]. However, there is no formal derivation available in favour of the particular choice of these distributions, and hence, they are chosen heuristically.…”
Section: Introductionmentioning
confidence: 99%